PENGARUH KOMPENSASI MANAJEMEN, PERJANJIAN HUTANG DAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - TANOMI, REHOBOT (: 2303-1719)
This study aims to examine the effect of management compensation, debt covenant and tax on earnings management on public companies in Indonesia. For earnings management practice, there are two role which is principal (stockholder) and agent (manager). This practice happens because of the interest conflict between principal and agent where their own interest is to maximize their own profit. The samples used are 15 manufacturing companies listed in BEI and had financial statements between year 2007 to 2009. The data analysis using multiple regression analysis. The results of this study indicate that management compensation, debt covenant and tax on earnings management simultaneously have a significant effect on earnings management but however as partially compensation management has the effect still can be proved, as for debt covenant and tax doesn’t have any effect.